O Criminal Compliance e a Autorregulação Regulada: uma análise jus-filosófica do giro conceitual da responsabilidade penal em uma sociedade globalizada - Deveikis, Gabriel Druda (2019)
Article 13, § 2, items "a", "b" and "c" of Decree-Law no. 2.848/1940 (Penal/Criminal Code) is part of the "Title II - THE CRIME", dealing with the causal relationship (caput) and the relevance of the omission (§ 2 and respective paragraphs). The mentioned article is the legal framework of the omission that is criminally relevant in Brazilian Criminal Law. The present dissertation is intended to analyze and also establish the limits of said legal provision particularly regarding the professional activities developed by the position of chief compliance officer. In order to do so, the present dissertation starts from the discussion of a broader theme, that is, that surrounds the main problem, which is the analysis of the philosophical origin and the legal origin of the phenomena denominated compliance, as well as the approach to economic crime as the product of a globalized world. The present dissertation then goes on to present a detailed study of compliance under the Criminal Law, analyzing, in a detailed way, the legal frameworks of criminal compliance, both in Brazil and abroad, as well as the criminal legislations impose the position of chief compliance officer. Having introduced the present study in the discussion of the criminal implications of the position of chief compliance officer based on Brazilian and international legislation, we proceed to analyze in depth the main problem brought by this dissertation: the limits of omission relevant to that position. Thus, it is addressed to the first, the importance that documents whose legal nature is not of Criminal Law have as regards the delimitation of criminal responsibility for omission of the position of chief compliance officer. At this point, this dissertation also conceptualizes the so-called compliance programs and deeply analyzes the role they play in relation to the aforementioned position. Finally, the present study goes into the discussion of the criminal omission and, consequently, the legal duty to act, bringing a dense bibliographical foreshortening of the concept of omission in Criminal Law. After having extensively covered the issue of criminal omission in the field of Criminal Law as a whole, this dissertation inserts the debate on the reality of the activities carried out by the chief compliance officer, identifying limits to criminal liability for omission of the individual occupier of said position.